Study guides

☆☆

Q: How do you simplify X2 plus 2x plus 4?

Write your answer...

Submit

Still have questions?

Related questions

(x - 6) (x + 4) = x2 - 2x - 24

x= -3

x3 + x2 - 6x + 4 = (x - 1)(x2 + 2x - 4)

I'm answering this based on the way you wrote it. If you meant something different, please substitute words where necessary. x2-2x+4+2x+1-x62+5=2x-2x+4+2x+1-62x+5=-60x+10

x^5+2x^4+4x^2+2x-3

3x2 + 2x + 3 + x2 + x + 1 = 4x 2+ 3x + 4

negative four: x2 - 2x + 5 = x2 - 2x + 5 - 4 = x2 - 2x + 1 = (x - 1)2

(3x4 + 2x3 - x2 - x - 6)/(x2 + 1)= 3x2 + 2x - 4 + (-3x - 2)/(x2 + 1)= 3x2 + 2x - 4 - (3x + 2)/(x2 + 1)where the quotient is 3x2 + 2x - 4 and the remainder is -(3x + 2).

It depends what x equals, unless you know that it's impossible to answer the question past "2x + 4"

x2+10x+1 = -12+2x x2+8x+13 = 0 The solution: x = -4 + the square root of 3 or x = -4 - the square root of 3

x2+10x+1 = -12+2x x2+10x-2x+1+12 = 0 x2+8x+13 = 0 Solving by using the quadratic equation formula: x = - 4 - or + the square root of 3

By collecting like terms: 8z+4-2x